Two-Wheel Traction Control for Electric Vehicles - Sahbani, Abdelaziz; ., . (International Journal of Engineering and Technology, 2018)
This paper deals with a detailed dynamic design of traction control strategies based on fuzzy logic controller. The proposed system is motorized by two independent DC motors associated with two static DC converters and an electrical differential. An approach to both longitudinal and lateral controls of two wheels is described. In fact, by using electric motors, it is possible to have a torque control in each wheel drive, enabling the implementation of a traction control. Consequently, the stability and the safety of the vehicle will be improved. Obtained simulation results confirm the efficiency of the proposed controller.Â